K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

AH
Akai Haruma
Giáo viên
8 tháng 8 2020

Lời giải:

a)

$A=-(x^3y^5z^2):(-x^6y^9z^3)$

$=(x^3:x^6)(y^5:y^9)(z^2:z^3)$

$=x^{-3}y^{-4}z^{-1}=\frac{1}{x^3y^4z}=\frac{1}{1^3.(-1)^4.100}=\frac{1}{100}$

b)

$B=(\frac{3}{4}:\frac{-1}{2}).[(x-2)^3(2-x)]$

$=\frac{-3}{2}[-(x-2)^3(x-2)]=\frac{3}{2}(x-2)^4=\frac{3}{2}(3-2)^4=\frac{3}{2}$

c)

$x-y-z=17-16-1=0$

$\Rightarrow (x-y-z)^5=0$

$(-x+y-z)^3=(-17+16-1)^3=(-2)^3=-8$

$\Rightarrow C=0$

18 tháng 6 2015

a)5x2y-10xy2

=5xy(x-2y)

b,:4x(2y-z)+7y(z-2y)

=4x(2y-z)-7y(2y-z)

=(2y-z)(4x-7y)

c,:y(x-z)+7(z-x)

=y(x-z)-7(x-z)

=(x-z)(y-7)

d)36-12x+x^2​

=x2-2.x.6+62

=(x-6)2

e) (x-5)^2-16

=(x-5)2-42

=(x-5-4)(x-5+4)

=(x-9)(x-1)

f) ​8x^3+1/27

=(2x)3+(1/3)3

=(2x+1/3)(4x2+2/3.x+1/9)

30 tháng 9 2017

1)

a \(x^3+y^3+x^2z+y^2z-xyz\)

=(x+y)(x2-xy+y2)+z(x2-xy+y2)

=(x+y+z)(x^2-xy+y^2)

b)yz(y+z)+xz(z-x)-xy(x+y)

=yz2+y2z+xz2-x2z-x2y-xy2

=z2(x+y)-z(x2-y2)-xy(x+y)

=(z2-xy)(x+y)-z(x-y)(x+y)

=(z2-xy-zx+zy)(x+y)

=[z(z-x)+y(z-x)](x+y)

=(z+y)(z-x)(x+y)

30 tháng 9 2017

==1)

a) x3+y3+x2z+y2z-xyz

= ( x+y)(x2-xy+y2)+z(x2+y2-xy)

=(x2+y2-xy)(x+y+z)

b) yz(y+z)+xz(z-x)-xy(x+y)

=y2z+yz2+xz(z-x)-x2y-xy2

=(y2z-xy2)+(yz2-xy2)+xz(z-x)

=y2(z-x)+y(z2-x2)+xz(z-x)

=(z-x)(y2+xz)+y(z+x)(z-x)

=(z-x)(y2+xz+yz+xy)

=(z-x)(y(y+z)+x(z+y))

=(z-x)(y+z)(x+y)

3 tháng 6 2017

x2-2xy+y2-z2+2zt-t2

=(x2-2xy+y2)-(z2-2zt+t2)              

=(x-y)2-(z-t)2

=(x-y+z-t)(x-y-z+t)   

3 tháng 6 2017

   x2 – 2xy + y2 – z2 + 2zt – t2 = (x2 – 2xy + y2) – (z2 – 2zt + t2)

= (x – y)2 – (z – t)2

= [(x – y) – (z – t)] . [(x – y) + (z – t)]

= (x – y – z + t)(x – y + z – t)

23 tháng 11 2017

Ta có :

\(1)\left(x^2+y^2-5\right)-4x^2y^2-16xy-16\)

\(=\left(x^2+y^2-5\right)^2-[\left(2xy\right)^2+2.2xy.4+4^2]\)

\(=\left(x^2+y^2-5\right)^2-\left(2xy+4\right)^2\)

\(=\left(x^2+y^2-5-2xy-4\right)\left(x^2+y^2-5+2xy+4\right)\)

\(=\left(x^2+y^2-2xy-9\right)\left(x^2+y^2+2xy-1\right)\)

\(=\left[\left(x-y\right)^2-3^2\right]\left[\left(x+y\right)^2-1\right]\)

\(=\left(x-y+3\right)\left(x-y-3\right)\left(x+y-1\right)\left(x+y+1\right)\)

\(2)x^2y^2\left(y-x\right)+y^2z^2\left(z-y\right)-z^2x^2\left(z-x\right)\)

\(=x^2y^2\left(y-z+z-x\right)+y^2z^2\left(z-y\right)-z^2x^2\left(z-x\right)\)

\(=x^2y^2\left(y-z\right)+x^2y^2\left(z-x\right)+y^2z^2\left(z-y\right)-z^2x^2\left(z-x\right)\)

\(=\left(y-z\right)\left(x^2y^2-y^2z^2\right)+\left(z-x\right)\left(x^2y^2-z^2x^2\right)\)

\(=\left(y-z\right)\left(xy-yz\right)\left(xy+yz\right)+\left(z-x\right)\left(xy-zx\right)\left(xy+xz\right)\)

\(=y^2\left(y-z\right)\left(x-z\right)\left(x+z\right)+x^2\left(z-x\right)\left(y-z\right)\left(y+z\right)\)

\(=\left(y-z\right)\left(x-z\right)[y^2\left(x+z\right)-x^2\left(y+z\right)]\)

\(=\left(y-z\right)\left(x-z\right)(y^2x+y^2z-x^2y-x^2z)\)

\(=\left(y-z\right)\left(x-z\right)[(y^2x-x^2y)+(y^2z-x^2z)]\)

\(=\left(y-z\right)\left(x-z\right)[xy(y-x)+z(y^2-x^2)]\)

\(=\left(y-z\right)\left(x-z\right)[xy(y-x)+z(y-x)\left(x+y\right)]\)

\(=\left(y-z\right)\left(x-z\right)(y-x)\left(xy+xz+yz\right)\)

5 tháng 11 2018

b)\(x^2\left(y-z\right)+y^2\left(z-x\right)+z^2\left(x-y\right)\)

=\(x^2y-x^2z+y^2z-y^2x+z^2\left(x+y\right)\)

\(=z^2\left(x-y\right)+\left(x^2y-y^2x\right)-\left(x^2z-y^2z\right)\)

=\(z^2\left(x-y\right)+xy\left(x-y\right)-z\left(x^2-y^2\right)\)

\(=z^2\left(x-y\right)+xy\left(x-y\right)-z\left(x-y\right)\left(x+y\right)\)

\(=\left(x-y\right)\left(z^2+xy-zy-zx\right)\)

\(=\left(x-y\right)\left[z\left(z-x\right)-y\left(z-x\right)\right]\)

\(=\left(x-y\right)\left(z-y\right)\left(z-x\right)\)